Pengaruh Efektivitas Sekolah Menengah Atas Terhadap Peluang Masuk Universitas Negeri Jakarta: Studi Kasus Untuk Mahasiswa Fakultas Ilmu Sosial (International Forum of Researchers and Lecturers, 2023)
The results of this study aim to analyze the effectiveness opportunities for High School Students to enter the Jakarta State University. This research method uses qualitative research methods. The sources used for this research are interviews, filling out questionnaires and collecting data from several relevant journals and articles. This research focuses more on how students get motivated and the driving factors related to entering State Universities. The results of this study explain that the data obtained from the interview results assume that the facility factors from the school, environmental factors within the school and external support are the dominant reasons for students to continue their education to State Universities.